Initiating a Science Reading Program in a Ghetto High School Role of the Science Reading Consultant - Newman, Harold; Jersey City State Coll., NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This is a report of an effort to improve ghetto children's reading in science classes. The writer worked as a consultant with ninth grade general science teachers. The teachers involved in this study used lessons designed by the consultant, as well as materials from commercial publishers. The author reports that there was marked improvement in the attitudes, understandings, and actions of all members of the Science Department since the inception of the project. (BR)
Educational level discussed: Grade 9.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Grade 9.; Reading Instruction; Secondary School Science; General Science; Ghettos; Reading Difficulty; Reading Research; New Jersey Bell Telephone Reading Project